A configurable evaluation system for PLC experiments deployed on cloud. Issue 6 (9th April 2021) - Zhang, Shirong; Tang, Yuling
Abstract: Programmable logic controller (PLC) is always set as a professional course of automation‐related majors in Chinese universities and colleges. Abundant experiments are required to ensure that the students are sufficiently trained to get qualified practical skills and engineering abilities. The evaluation of abundant PLC experiments is a heavy and time‐consuming task, and it is hard to grade an experiment result precisely and fairly. In this paper, a cloud‐based automatic evaluation system for PLC experiments is accordingly proposed to deal with the above problems. Aliyun is employed to build the system platform. During experiments, client threads on the cloud will be scheduled to accesses the on‐site S7‐1500 PLCs through OLE for process control (OPC) UA protocol. Further, an innovative section‐based experiment management method is proposed to make the system open, configurable, and thus extendable. The system relieves the hard work of the teachers on experiment evaluation and provides accurate evaluation conclusions. In contrast, the students can get more comprehensive feedback information and advice from the system to better understand the experiments and the behind principles. The cloud‐based framework, the standard protocol as OPC UA, and the configurability of the system can be good references for other relevant systems.